2009
DOI: 10.1002/stem.187
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Mesenchymal Stem Cell Tropism for Tumor and Wounding Microenvironments Using In Vivo Bioluminescent Imaging

Abstract: Multipotent mesenchymal stromal/stem cells (MSC) have shown potential clinical utility. However, previous assessments of MSC behavior in recipients have relied on visual detection in host tissue following sacrifice, failing to monitor in vivo MSC dispersion in a single animal and limiting the number of variables that can be observed concurrently. In this study, we utilized noninvasive, in vivo bioluminescent imaging to determine conditions under which MSC selectively engraft in sites of inflammation. MSC modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
483
3
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(519 citation statements)
references
References 54 publications
23
483
3
10
Order By: Relevance
“…7 Tumor-directed migration and incorporation of MSCs have been demonstrated in a number of preclinical studies in vitro using transwell migration assays, and in vivo using animal tumor models. The homing capacity of MSCs has been demonstrated with almost all tested human cancer cell lines, including lung cancer, 8 malignant gliomas, 9--11 Kaposi's sarcomas, 12 breast cancer, 13,14 colon carcinoma, 15 pancreatic cancer, 16,17 melanoma 18 and ovarian cancer. 13 Engineered with tumor-specific anticancer genes, MSCs are capable of producing anticancer agents locally and constantly at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Tumor-directed migration and incorporation of MSCs have been demonstrated in a number of preclinical studies in vitro using transwell migration assays, and in vivo using animal tumor models. The homing capacity of MSCs has been demonstrated with almost all tested human cancer cell lines, including lung cancer, 8 malignant gliomas, 9--11 Kaposi's sarcomas, 12 breast cancer, 13,14 colon carcinoma, 15 pancreatic cancer, 16,17 melanoma 18 and ovarian cancer. 13 Engineered with tumor-specific anticancer genes, MSCs are capable of producing anticancer agents locally and constantly at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…The homing capacity of MSCs has been demonstrated with almost all tested human cancer cell lines, including lung cancer, 8 malignant gliomas, 9--11 Kaposi's sarcomas, 12 breast cancer, 13,14 colon carcinoma, 15 pancreatic cancer, 16,17 melanoma 18 and ovarian cancer. 13 Engineered with tumor-specific anticancer genes, MSCs are capable of producing anticancer agents locally and constantly at the tumor site. One such anticancer agent comes from the tumor necrosis factor (TNF)-related apoptosisinducing ligand (TRAIL), a member of the TNF super-family.…”
Section: Introductionmentioning
confidence: 99%
“…50 Furthermore, several studies have demonstrated MSC tropism on tumors, and our recent work also proved that MSCs can recruit macrophages and promote tumor growth. 24,51,52 Emerging evidence supports the idea that induction of mutations in stromal cells can promote tumor formation. Genetic mutations in stromal cells have been reported in breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Il faut cependant nuancer ces observations par le fait que ce tropisme n'est pas forcĂ©ment toujours spĂ©cifique de la tumeur ellemĂȘme. En effet, l'Ă©quipe du docteur F. Marini a notamment montrĂ© que les CSM sont en fait capables de migrer de maniĂšre plus gĂ©nĂ©rale vers les sites d'inflammation consĂ©cutifs soit Ă  une blessure soit au dĂ©veloppement d'une tumeur [11]. D'autre part, ces auteurs ont aussi montrĂ© que les CSM injectĂ©es dans la circulation chez des souris intactes avaient un tropisme naturel pour le poumon, le foie et la rate [11].…”
Section: Tropisme Des Csm Pour Les Sites Tumorauxunclassified
“…En effet, l'Ă©quipe du docteur F. Marini a notamment montrĂ© que les CSM sont en fait capables de migrer de maniĂšre plus gĂ©nĂ©rale vers les sites d'inflammation consĂ©cutifs soit Ă  une blessure soit au dĂ©veloppement d'une tumeur [11]. D'autre part, ces auteurs ont aussi montrĂ© que les CSM injectĂ©es dans la circulation chez des souris intactes avaient un tropisme naturel pour le poumon, le foie et la rate [11]. Or, une telle comparaison de souris non manipulĂ©es Ă  des souris porteuses de tumeurs a rarement Ă©tĂ© effectuĂ©e dans les Ă©tudes antĂ©rieures.…”
Section: Tropisme Des Csm Pour Les Sites Tumorauxunclassified